Analisis Penyusunan Soal Maharah Istima’ dan Maharah Qiraah Kelas VII MTs Al-Hikmah Purwoasri - Fitrah Dinanti Massofia; Habibullah Muhammad; Dyah Ayu Khoirunnisa; Arina Elma Husna; Nur Qomari (Jurnal Pendidikan Bahasa Arab, 2024)
This research aims to implement 1) the stage of preparing test items, 2) preparing maharah istima' and maharah qiraah questions. This research uses a descriptive qualitative approach. Data collection was carried out by observation, interviews and documentation at MTs Al Hikmah Purwoasri Kediri. After the data was collected, data analysis was carried out using the model from Miles and Huberman, namely: 1) data reduction, 2) data presentation, 3) drawing conclusions/verification so that research results were obtained that 1) each test or question prepared must refer to question grid. After knowing the steps for preparing further questions in writing the test, you must follow the rules or writing rules. 2) creating instruments in the form of maharah istima' and maharah qiraah questions is carried out by referring to learning indicators, in this case Arabic language learning. This means that the tests or questions prepared must not deviate from the learning indicators.